Search for low-mass dilepton resonances in Higgs boson decays to four-lepton final states in proton–proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Bergauer, T.; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (The European physical journal C)
A search for low-mass dilepton resonances in Higgs boson decays is conducted in the four-lepton final state. The decay is assumed to proceed via a pair of beyond the standard model particles, or one such particle and a Z boson. The search uses proton-proton collision data collected with the CMS detector at the CERN LHC, corresponding to an integrated luminosity of 137 fb(-1), at a center-of-mass energy root s = 13 TeV. No significant deviation from the standard model expectation is observed. Upper limits at 95% confidence level are set on model-independent Higgs boson decay branching fractions. Additionally, limits on dark photon and axion-like particle production, based on two specific models, are reported.